Pengaruh Akuntabilitas, Transparansi, dan Partisipasi Orang Tua Terhadap Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di MAN 1 Surakarta - Meilans Dita Pratiwi; Muhammad Hasan Ma’ruf; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2027)
This study aims to examine the effect of accountability, transparency, and parental participation on effectiveness of School Operational Assistance fund management at MAN 1 Surakarta. The research employs a quantitative approach using primary data collected through questionnaires distributed to students at respondents. The sampling technique used is Probability Sampling with the Stratified Random Sampling method, resulting in total sample 93 descriptive statistics, data quality test (validity and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), and multiple linear regression analysis accompanied by hypothesis testing (F-test, t-test, and coefficient of determination/ R²) using SPSS software. The results show that accountability has positive and significant effect on the effectiveness of BOS fund management, while transparency does not have a significant effect significant and parental participation also does not have a significant effect on the effectiveness of BOS fund management. Coefficient of determination (R²) of 0,617, indicating that accountability, transparency, and parental participation explain 61,7% of the variation in effectiveness of BOS fund management, while the remaining 38,3% is influenced by other factors outside the research model.